2012
DOI: 10.1177/1071181312561299
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Dual vs. Single Monitor Use during Common Office Tasks

Abstract: Previous studies have found that using multiple monitors increases productivity, but there are also documented drawbacks to increased monitor count and/or size. The purpose of this study was to determine whether increases in productivity hold true with newer technology, like wide flat-screens, in the multitasking context. Sixty participants were asked to complete several tasks commonly completed in an office environment. These tasks were performed on four different monitor configurations: a single and dual 17"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…Ling et al [65] found that the number of window switches decreased. And Czerwinski et al [15] suggested that multi-display environments allowed users to "engage in more complex multitasking behavior", whilst numerous papers have noted benefits of having "abundant" display spaces [56] in terms of spatial memory [94] and performance across a variety of productivity tasks [13,51,55,65,80,106].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ling et al [65] found that the number of window switches decreased. And Czerwinski et al [15] suggested that multi-display environments allowed users to "engage in more complex multitasking behavior", whilst numerous papers have noted benefits of having "abundant" display spaces [56] in terms of spatial memory [94] and performance across a variety of productivity tasks [13,51,55,65,80,106].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study showed elevated neck flexion and head tilt and smaller range of movement when using a laptop versus a desktop computer (Straker, Jones, & Miller, 1997), although another study found no difference between both in physical exposure and performance (Moffet, Hagberg, Hansson-Risberg, & Karlqvist, 2002). In addition, computer workstations with multiple monitors have also been gaining popularity, and studies show benefits in terms of productivity and user satisfaction (Kang & Stasko, 2008; Owens et al, 2012; Poder, Godbout, & Bellemare, 2011; Truemper et al, 2008). However, few investigations have provided data to objectively determine how they affect MSD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Another important consideration is input and output interfaces. Many of us work remotely on small laptop screens, even though multiple monitors or one large monitor can substantially improve productivity and satisfaction [7]. This is especially the case when a lot of screen real estate is taken up by a videoconferencing application.…”
Section: Physical Resources For Online Engagementmentioning
confidence: 99%